Coming to Terms with Superdiversity The Case of Rotterdam - Scholten, Peter; Crul, Maurice; van de Laar, Paul.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This open access book discusses Rotterdam as clear example of a superdiverse city that is only reluctantly coming to terms with this new reality. Rotterdam, as is true for many post-industrial cities, has seen a considerable backlash against migration and diversity: the populist party Leefbaar Rotterdam of the late Pim Fortuyn is already for many years the largest party in the city. At the same time Rotterdam has become a majority minority city where the people of Dutch descent have become a numerical minority themselves. The book explores how Rotterdam is coming to terms with superdiversity, by an analysis of its migration history of the city, the composition of the migrant population and the Dutch working class population, local politics and by a comparison with Amsterdam and other cities. As such it contributes to a better understanding not just of how and why super-diverse cities emerge but also how and why the reaction to a super-diverse reality can be so different. By focusing on different aspects of superdiversity, coming from different angles and various disciplinary backgrounds, this book will be of interest to students and scholars in migration, policy sciences, urban studies and urban sociology, as well as policymakers and the broader public.
1 Introduction - Peter Scholten, Maurice Crul and Paul van de Laar -- PART I: SUPERDIVERSITY IN ROTTERDAM: 2 Rotterdam's superdiversity from a historical perspective (1600-1980) - Paul van de Laar and Arie van der Schoor -- 3 The second and third generation in Rotterdam: increasing diversity within diversity - Maurice Crul, Frans Lelie and Elif Keskiner -- 4 Between choice and stigma: Identifications of economically successful migrants - Marianne van Bochove and Jack Burgers -- PART II: ROTTERDAM'S RESPONSE TO SUPERDIVERSITY: -- 6 'Walking the walk' rather than 'talking the talk' of superdiversity: Continuity and change in the development of Rotterdam's immigrant integration policies - Rianne Dekker & Ilona van Breugel -- 7 Laboratory Rotterdam. Logics of exceptionalism in the governing of urban populations - Friso van Houdt & Willem Schinkel -- 8 Rotterdam as a case of complexity reduction: Migration from Central and Eastern European countries - Erik Snel, Mark van Ostaijen & Margrietha 't Hart. -- PART III: ROTTERDAM IN COMPARATIVE PERSPECTIVE: -- 9.A tale of two cities: Rotterdam, Amsterdam and their immigrants - Han Entzinger -- 10. The 'integration' of people of Dutch descent in superdiverse neighbourhoods - Maurice Crul and Frans Lelie -- 11. Superdiversity and city branding: Rotterdam in perspective - Warda Belabas and Jasper Eshuis -- 12. Conclusions: Coming to terms with superdiversity? - Maurice Crul, Peter Scholten and Paul van de Laar -- 13. Epilogue: What's the matter with Rotterdam? - Steve Vertovec.
Keywords: Emigration and immigration; Political science; Cities and towns -- History; Human Migration; Political Science; Urban History